Role of NTFP-based Micro-enterprises in Livelihood Improvement of Forest User Group: A Case of a Sishnoobased Micro-enterprise in the Mid-hills of Nepal - Rajbhandari, Sujan; Yadav, Yogendra; Shrestha, Prerana; Dahal, Deepa; Sharma, Garima; Poudel, Sanjay; Basnet, Reecha (Journal of Forest and Livelihood, 2025)
The research delves into the impact of non-timber forest products (NTFPs) on rural livelihoods, with a specific focus on the Sishnoo powder enterprise situated within the Pairakhet community forest in Nepal. Employing a combination of primary data collection techniques such as surveys and interviews alongside secondary data from diverse sources, the study meticulously evaluates the benefit-cost ratio of the enterprise. Moreover, it employs sophisticated statistical analyses, including the Likert Scale and Kendall Tau test, to gauge users' perceptions regarding the enterprise's influence on economic and social conditions. By scrutinising the economic, social, and human dimensions of livelihoods, the study unveils notable positive transformations, mainly in employment generation and skill enhancement. Sishnoo-based micro-enterprises emerges as a potent agent for bolstering economic prosperity and fostering capacity building, especially among marginalised communities. The findings underscore the critical necessity for nurturing NTFP-based micro-enterprises and implementing targeted business awareness initiatives to fortify rural livelihoods comprehensively.